Evidence for a Dual-Pathway, 2-Hit Genetic Model for Focal Cortical Dysplasia and Epilepsy. (February 2022) - Bennett, Mark F.; Hildebrand, Michael S.; Kayumi, Sayaka; Corbett, Mark A.; Gupta, Sachin; Ye, Zimeng; Krivanek, Michael; Burgess, Rosemary; Henry, Olivia J.; Damiano, John A.; Boys, Amber; Gécz, Jozef; et al.
Abstract : Background and Objectives: The 2-hit model of genetic disease is well established in cancer, yet has only recently been reported to cause brain malformations associated with epilepsy. Pathogenic germline and somatic variants in genes in the mechanistic target of rapamycin (mTOR) pathway have been implicated in several malformations of cortical development. We investigated the 2-hit model by performing genetic analysis and searching for germline and somatic variants in genes in the mTOR and related pathways. Methods: We searched for germline and somatic pathogenic variants in 2 brothers with drug-resistant focal epilepsy and surgically resected focal cortical dysplasia (FCD) type IIA. Exome sequencing was performed on blood- and brain-derived DNA to identify pathogenic variants, which were validated by droplet digital PCR. In vitro functional assays of a somatic variant were performed. Results: Exome analysis revealed a novel, maternally inherited, germline pathogenic truncation variant (c.48delG; p.Ser17Alafs*70) in NPRL3 in both brothers. NPRL3 is a known FCD gene that encodes a negative regulator of the mTOR pathway. Somatic variant calling in brain-derived DNA from both brothers revealed a low allele fraction somatic variant (c.338C>T; p.Ala113Val) in the WNT2 gene in 1 brother, confirmed by droplet digital PCR. In vitro functional studies suggested a loss of WNT2 function as a consequence of this variant. A second somatic variant has not yet been found in the other brother. Discussion: We identify a pathogenic germline mTOR pathway variant ( NPRL3 ) and a somatic variant ( WNT2 ) in the intersecting WNT signaling pathway, potentially implicating the WNT2 gene in FCD and supporting a dual-pathway 2-hit model. If confirmed in other cases, this would extend the 2-hit model to pathogenic variants in different genes in critical, intersecting pathways in a malformation of cortical development. Detection of low allele fraction somatic second hits is challenging but promises to unravel the molecular architecture of FCDs.